Honduras : Statistical Annex. (IMF Staff Country Reports; Country Report, 2000)
The statistical data on national accounts, origin of gross domestic product, financing of investment, composition of fixed capital formation, statistics on selected agricultural products, labor force by sector, consolidated operations of the non financial public sector, and central government revenue of Honduras are presented in this paper. The data on operations of the social security institute, operations of the local governments, operations of national enterprise of electricity energy, visible trade with the Ccentral American Common Market, and related economic indices are also presented.